Diabetic Pilon Factures: Are They as Bad as We Think?. Issue 3 (March 2021) - Oladeji, Lasun O.; Platt, Brooks; Crist, Brett D.
Abstract : Objective: To identify how diabetes impacts the risk of complications requiring further surgery (deep surgical site infection, nonunion, amputation, and arthrodesis) after pilon fracture fixation. Design: Retrospective cohort study. Setting: Level 1 academic trauma center. Patients: Two hundred seventy-nine pilon fractures (276 patients) were identified. A retrospective review was performed to find patients who presented for open reduction and internal fixation of a tibial pilon fracture (OTA/AO 43). Patient demographics, medical comorbidities, OTA/AO fracture type, and surgical outcomes were reviewed. Intervention: Patients were stratified into cohorts based on the presence or absence of diabetes at the time of surgery. Main Outcome Measurements: The complications of interest that proved significant during univariate analyses were then entered into a multivariable logistic regression model using a stepwise method to identify the independent predictors for complications. Results: There were 43 fractures (15.4%) in patients with diabetes mellitus; 17 (39.5%) of whom were insulin-dependent diabetics. Diabetic patients were significantly more likely to have a higher body mass index (34.81 vs. 29.57, P = 0.002) and be older (55.30 ± 16.3 years vs. 41.70 ± 14.05, P < 0.001) at the time of injury. Patients without diabetes were more likely to sustain an OTA/AO 43-C3 fracture (36.0% vs. 11.6%, P = 0.001). Diabetic patients were 5.5 times more likely to require an arthrodesis [95% confidence interval (CI) = 1.894–16.214; P = 0.001] and 2.7 times more likely to develop a deep infection (95% CI = 1.261–5.630; P = 0.008). Conclusions: Overall, diabetic patients in this study were 3.64 times more likely (95% CI = 1.854–7.159; P < 0.001) to experience any complication, despite having less complex fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.